A speech reception in noise test for preschool children (the Galker-test): Validity, reliability and acceptance. Issue 10 (October 2015) - Lauritsen, Maj-Britt Glenn; Kreiner, Svend; Söderström, Margareta; Dørup, Jens; Lous, Jørgen
Abstract: Purpose: This study evaluates initial validity and reliability of the "Galker test of speech reception in noise" developed for Danish preschool children suspected to have problems with hearing or understanding speech against strict psychometric standards and assesses acceptance by the children. Methods: The Galker test is an audio-visual, computerised, word discrimination test in background noise, originally comprised of 50 word pairs. Three hundred and eighty eight children attending ordinary day care centres and aged 3–5 years were included. With multiple regression and the Rasch item response model it was examined whether the total score of the Galker test validly reflected item responses across subgroups defined by sex, age, bilingualism, tympanometry, audiometry and verbal comprehension. Results: A total of 370 children (95%) accepted testing and 339 (87%) completed all 50 items. The analysis showed that 35 items fitted the Rasch model. Reliability was 0.75 before and after exclusion of the 15 non-fitting items. In the stepwise linear regression model age group of children could explain 20% of the variation in Galker-35-score, sex 1%, second language at home 4%, tympanometry in best ear 2%, and parental education another 2%. Other variable did not reach significance. Conclusion: The Galker-35 was well accepted by children down to the age of 3 years and results indicate that the scale represents construct valid and reliable measurement.